Percutaneous Biliary Interventions in Pediatric Patients - Vogt, Katharina; Hammer, Simone; Grözinger, Gerd; Knott, Emily A.; Uller, Wibke (Digestive Disease Interventions, 2024)
Percutaneous biliary interventions have become standard for a variety of indications in pediatric patients. They offer a minimally invasive approach to managing biliary pathologies often associated with liver transplantation and hepatobiliary surgery. Interventions include the insertion of drainage catheters for bilomas, percutaneous transhepatic cholangiography for diagnostic purposes, and percutaneous transhepatic biliary drainage for the treatment of biliary leaks and cholestasis. Sonography, computed tomography, and fluoroscopy are used to guide the procedures. This review aims to demonstrate the indications and technical aspects of percutaneous biliary interventions in pediatric patients with a special focus on radiation protection.
Keywords: biliary intervention; pediatric; PTBD in children; biliary drainage; interventional radiology